2013
DOI: 10.1080/13648470.2012.747594
|View full text |Cite
|
Sign up to set email alerts
|

‘My wife, you are supposed to have a rest now’: an analysis of norms influencing men's role in prenatal care in south-eastern Tanzania

Abstract: Men as sexual partners, fathers and household heads have a direct bearing on women's reproductive health. However, little is known about the influence of changing norms and values on men's role in ensuring women's health during pregnancy and childbirth. This study from rural south-eastern Tanzania explores men's and women's discussions on men's roles and responsibilities in prenatal care and links them to an analysis of norms and values at the household level and beyond. Data from eight focus group discussions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
3
15
0
2
Order By: Relevance
“…Men were in charge of providing for the family and they were expected to fulfill this role during the postpartum period, as well as at other times. Our findings are similar to those of other studies, which show that men are the main breadwinners and women depend on them for economic support [38,48,56,57]. This study also points out that men were not the most involved in ‘caring’ and household work while the postpartum mother was convalescing.…”
Section: Discussionsupporting
confidence: 92%
“…Men were in charge of providing for the family and they were expected to fulfill this role during the postpartum period, as well as at other times. Our findings are similar to those of other studies, which show that men are the main breadwinners and women depend on them for economic support [38,48,56,57]. This study also points out that men were not the most involved in ‘caring’ and household work while the postpartum mother was convalescing.…”
Section: Discussionsupporting
confidence: 92%
“…The community members understood that these conditions could affect anyone and may lead to death. However, financial power and gender roles contribute to inadequate birth preparedness (22, 3739). A previous study in the same region showed that men are the decision-makers concerning complying with referral advice, and the woman have little or no voice in these decisions, regardless of her becoming suspicious of a potentially dangerous situation during pregnancy or delivery (40).…”
Section: Discussionmentioning
confidence: 99%
“…Men's roles in family and marriage structures were changing which led to contradictions in this society. Men saw themselves as financially responsible, or as the family "breadwinners" despite often being unable to cover the costs of prenatal care (Gross et al, 2013). Although this study provides some evidence as to how fathers may view their role during pregnancy, it is unknown whether American fathers would share this same viewpoint.…”
Section: Review Of Literaturementioning
confidence: 85%
“…One study explored fathers' roles during pregnancy in rural southeastern Tanzania (Gross et al, 2013). Men's roles in family and marriage structures were changing which led to contradictions in this society.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation